Dialog znaków i kodów: między oryginałem a polskim przekładem w powieści Miljenko Jergovicia Ruta Tannenbaum - Czerwiński, Maciej (Przekłady Literatur Słowiańskich, 2011)
A Dialogue of Signs and Codes: between Jergović’s Novel Ruta Tannenbaum and the Polish Translation In the article the novel Ruta Tannenbaum, written by Croatian and Bosnian-Herzegovinian author Miljenko Jergović, and the translation of the novel into Polish by Magdalena Petryńska is analyzed. By comparing the original and the translation the question of dialogization of signs and cultural codes is taken into consideration. It is presented which aspects of the semantics of the literary work and the culture itself cannot be adequately adapted into the Polish language and Polish culture. Simultaneously, the idea of applying a semiotic and cultural semiotic approach in translatology in analyzed.